Nursing of Hypovolemia in Patients with Melena’s Hematemesis: A Case Study - Gracia Christy Fanuel Dian Ayu (Chakra Brahmanda Lentera Institute, 2022)
Background: Hematemesis melena is a patient’s condition with black stools or stools caused by upper gastrointestinal bleeding. Hypovolemic patients with hematemesis melena usually experience nausea, vomiting, and diarrhea. This study aims to describe nursing care for hypovolemia in patients with hematemesis melena. Methods: This research method uses a case study design. Data collection started from assessment to evaluation in the Kasuari ward of Simpang Lima Gumul Hospital in December 2021. The hematemesis melena patient was observed or treated for at least two days. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out using narrative analysis. Results: assessment of Mr. P with the main complaint complaining of vomiting blood for ±10 days, abdominal pain, weakness, black stools for ±10 days, and urinating for five days. The nursing diagnosis in the case of Mr. P is the actual diagnosis with priority hypovolemia related to functional fluid loss (D.0023). Nursing intervention for Mr. P was compiled based on the diagnosis of hypovolemia using pharmacological techniques such as antibiotics. Conclusion: The patient showed a not-so-significant decrease because the patient still had time to vomit blood and bloody stool.